LANGUAGE AND POWER: CRITICAL DISCOURSE ANALYSIS OF ARABIC TEXTBOOKS - Azis, Abdul; Uyuni, Yuyun Rohmatul; Syahid, Ahmad Habibi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
Arabic is one of the languages that has an important position in the context of religion, culture, and education in Indonesia, especially in the madrasah environment. Mastery of this language not only serves as a communication skill, but also as a medium to instill Islamic values and social norms inherent in the madrasah education system. Therefore, the selection and use of language in Arabic textbooks needs to be critically examined, especially related to aspects of power relations that can be implied in the learning text. This study aims to analyze the interaction of language and power contained in the Class IX Arabic textbook published by the Directorate of KSKK Madrasah, Directorate of Islamic Education, Ministry of Religious Affairs of the Republic of Indonesia in 2020. The research approach uses qualitative methods with critical discourse analysis focused on the study of linguistic elements, text structure, and socio-cultural contexts that form meaning and assert positions of power through language in the textbook. The research Data were obtained through the analysis of textbook texts, focusing on the identification of linguistic strategies used to establish and maintain certain ideologies and social norms. Meanwhile, the results showed that the language in the textbook contains elements that support the realization of institutional power and religious ideology through the choice of words, preparation of materials, and narrative constructs that are directed to form the attitude and understanding of learners in accordance with the values that want to be instilled by educational institutions. The findings of this study make an important contribution to the development of Arabic teaching materials that are not only oriented to the transfer of knowledge, but also able to open a reflective and critical space for hidden power relations in the learning language. Thus, learning materials are expected to support a more inclusive educational process and empower learners in the context of madrasah.